2018
DOI: 10.1002/jor.24124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sclerotic changes on stress concentration in early‐stage osteonecrosis: A patient‐specific, 3D finite element analysis

Abstract: Our results will clarify the pathogenic mechanism of collapse in ONFH. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…Kubo reported different collapse rates of 0%, 23%, and 81%, respectively, corresponding to different locations of lateral sclerotic boundary at the medial one‐third, the middle third, and the lateral one‐third of the weight‐bearing portion of the acetabulum, and he found that the anterior sclerotic boundary could also have an impact on the risk of collapse. Utsunomya generated patient‐specific FEM from 51 patients with ONFH, and he reported that stress was equally distributed on the femoral head surface in all FEM of ARCO Stage I hips, but stress was concentrated at the lateral boundary of the femoral head surface in all FEM of both ARCO Stages II and III hips, which is in accordance with the low‐intensity band on T1‐weighted MRI images, sclerotic changes on CT images and subchondral fractures on micro‐CT images. In this theory, the onset time of femoral head collapse begins at the repairing phase.…”
Section: Discussionmentioning
confidence: 99%
“…Kubo reported different collapse rates of 0%, 23%, and 81%, respectively, corresponding to different locations of lateral sclerotic boundary at the medial one‐third, the middle third, and the lateral one‐third of the weight‐bearing portion of the acetabulum, and he found that the anterior sclerotic boundary could also have an impact on the risk of collapse. Utsunomya generated patient‐specific FEM from 51 patients with ONFH, and he reported that stress was equally distributed on the femoral head surface in all FEM of ARCO Stage I hips, but stress was concentrated at the lateral boundary of the femoral head surface in all FEM of both ARCO Stages II and III hips, which is in accordance with the low‐intensity band on T1‐weighted MRI images, sclerotic changes on CT images and subchondral fractures on micro‐CT images. In this theory, the onset time of femoral head collapse begins at the repairing phase.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the HU values of the lateral boundary area in femoral heads with and without subsequent collapse after CT, ROI 2 was set as a 5.0 mm × 5.0 mm square in the lateral boundary area of demarcating sclerosis ( Figure 2E) where femoral head collapse usually occurs in ONFH. 16,17 In patients with Association Research Circulation Osseous (ARCO) stage 1 or those in whom lateral demarcating sclerosis was unclear even at stage 2, 6 the HU values in the area corresponding to the lateral boundary of the T1 low band in magnetic resonance imaging (MRI) were measured. The average HU value on three anteroposterior slices was used to decrease slicespecific differences in both ROI 1 and 2 ( Figure 2A).…”
Section: Setting the Region Of Interestmentioning
confidence: 99%
“…The necrosis of femoral head varies from cases to cases, thus appropriate classi cation is prerequisite for the modelling. The JIC classi cation is a direct evaluation method to re ect the relative position between necrotic lesions and the weight-bearing area [31][32][33] , and has been proved to be an appropriated classi cation to predict stress distribution of the hip joint in vivo 19,30,34,35 . In the JIC classi cation, Type C1 and C2 are recommended to undergo joint-preserving therapies, so both types were employed in this study.…”
Section: Discussionmentioning
confidence: 99%